Pengembangan media pembelajaran IPS berbasis android materi kerajaan dan peninggalan Hindu-Buddha - Meilia Tika Ayu Ningrum; Agus Purnomo; Idris Idris (University of Muhammadiyah Malang, 2021)
Android-based learning media for Social Studies (SS) might reduce boredom and accelerate student learning because it conveys attractive, creative, and innovative learning materials that support independent learning. This study aims to develop android-based learning media for SS about the Kingdom and Relics of Hindu-Buddhist. It employed Research and Development (R&D) with Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. Validation by material experts and linguists stated that the learning media was feasible with 61.5% and 70%. Results show that the learning media is suitable to use by 88.2%. The product trials resulted in practical products by 100% from educational practitioners, and 80.2% from students. This finding indicates that the media is effective, as can be seen, that 26 out of 32 students scored above the minimum grade. It is suggested that SS learning media are developed through further research by utilizing virtual reality technology. This may accelerate student understanding as the use of videos and pictures, and virtual reality to images and objects help depict things clearly.